2000
DOI: 10.1177/104973150001000404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interactive Multimedia Training on Knowledge, Attitudes, and Self-Efficacy of Social Work Students

Abstract: Objective Building Family Foundations (BFF), an interactive multimedia (1M) training curriculum for child welfare workers, and its use with baccalaureate social work students is described. Students’ attitudes toward technology and multimedia, instructional efficacy, and knowledge acquisition were examined. Method Social work students viewed selected units from BFF and completed pretests and posttests using the BFF Competency Rating Scale (CRS), the Child Welfare Knowledge Assessment (CWKA), and the Technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Online training offers a promising avenue for reaching the homeless services workforce by delivering ongoing, interactive, experiential, and flexible learning (Cauble and Thurston 2000; Kozma 1995). However, meta-analyses of studies comparing online and face-to-face training have either found no significant differences in the overall effectiveness of the two models in knowledge acquisition and retention (Zhao et al 2005) or great variation in outcomes; some applications of distance education perform better than their classroom counterparts, while others perform more poorly (Bernard et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Online training offers a promising avenue for reaching the homeless services workforce by delivering ongoing, interactive, experiential, and flexible learning (Cauble and Thurston 2000; Kozma 1995). However, meta-analyses of studies comparing online and face-to-face training have either found no significant differences in the overall effectiveness of the two models in knowledge acquisition and retention (Zhao et al 2005) or great variation in outcomes; some applications of distance education perform better than their classroom counterparts, while others perform more poorly (Bernard et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The enthusiasm for technology in higher education has been matched with an abundance of research designed to determine if the effort required for using various technologi- (Cauble & Thurston, 2000;Finn, 1995;Stocks & Freddolino, 1998); reduces anxiety concerning technology and computer use (Maki, Maki, Patterson, & Whittaker, 2000); is at least equally as effective as the traditional lecture format for teaching (Stocks & Freddolino, 1998;; and is perceived as helpful by students (Maki et al, 2000;Polloff & Pratt, 2001;Svanum, Chen, & Bublitz, 1997;Thurston, Denning, & Verschelden, 1996). Whether these positive results will endure once the novelty of technology in education wears off is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/termsand-conditions rooms'), computer-based instruction, distance learning and web-based courses that are often used to augment existing traditional face-to-face classroom teaching, and, interactive TV-ITV also referred to as compressed video, interactive video or videoconferencing (Freddolino, 1998;Forster & Rehner, 1998;Cauble & Thurston, 2000;Forster & Washington, 2000;Petracchi & Patchner, 2000, 2001Schoech, 2000;Hicks, 2002;Seabury, 2002). In the US, as distance education has been increasingly spreading in social work education, the Council of Social Work Education Commission on Accreditation established in 1994 a special committee to address quality issues of distance learning in the profession.…”
mentioning
confidence: 98%